Standardizing Competency Mapping To Improve Private Sector Bank Employee Performance In Thruchirapalli District: Bank Employee Performance In Thruchirapalli District - K. Vinoth; P. Gowthaman; S. Elango; R. Kannappa (International Journal of Computational and Experimental Science and Engineering, 2025)
In the evolving banking landscape, employee competency plays a crucial role in driving efficiency, customer satisfaction, and institutional growth. Private sector banks, characterized by their competitive work environment and performance-driven culture, require a robust competency mapping framework to assess employees’ skills and align them with organizational goals. However, existing assessment models in private banks often lack systematic evaluation, leading to inefficiencies in workforce management. This study aims to develop a structured competency mapping framework for private sector banks in Thruchirapalli district to bridge skill gaps and enhance employee productivity. Data were collected from 250 employees across five leading private banks, including ICICI, HDFC, Axis, Yes Bank, and Kotak Mahindra. The analysis utilized Exploratory Factor Analysis (EFA) and Structural Equation Modeling (SEM) to identify critical competency parameters such as technical expertise, leadership abilities, and customer relationship management. Findings from this study provide a standardized approach to competency mapping, enabling private banks to implement targeted training programs and career development strategies. The study concludes that competency-based human resource strategies significantly improve workforce efficiency and employee retention in private banking institutions.